A Comparison Study On Sand Filter With Membrane On Kitchen Waste Water - Aiman Luddin, Nik amirull; Pauzi, Ahmad Farhan; D.Rahman, Muhammad Hazim; Suwandi, Amir Khan; Abdul kadir, Muhammad Azraie (Multidisciplinary Applied Research and Innovation, 2022)
Grey water is defined as waste water from the kitchen, toilet, and dishwashing. This grey water can be purified using filtration process so that it can be used for other purposes. In order to get optimum quality of output filtration process, the combination of filter material are essential. The aim of this study is to create a kitchen waste water sand filter with a membrane. Kitchen waste water that was taken from residential students University Tun Hussein Onn Malaysia Pagoh campus. Silica sand, activated carbon, fiber and membrane are the material used for this filtration system. For this study, a total of 7 sample of kitchen waste water are used in order to get the best result with two different types of filter. For the overall test, all the filtering systems function well, leaving a favorable impression with the pure colour of the output water. The results show that Filter 1 that contains fine sand is the most suitable filter in filtering waste water as Ph, TDS and the color of the water after the filtering show a better result